(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Аnalyzed from the perspective of corruption, public procurement is one of the most critical sectors in the each economy. This statement can be applied to almost all legal-economic systems.This is due to the fact that there is no legal system in which there is no corruption in the field of public procurement.When it comes to this issue, the focus is on the efficiency of the systems for reducing the space for abuse in awarding public procurement contracts, ie reducing corruption. Comparatively, in other words, there is no national economy and no legal system, which, through the implementation of various control systems aren’t trying to reduce corruption. The mentioned control systems will be analyzed in this paper. With the dominant use of the analytical-descriptive method, as well as the comparative method, we will try to make an analysis of this question, emphasizing the "previous control" or known as "ex-ante" control. This kind of control created the main idea / motivation to deal with this issue. Namely, analyzing this question, with the help of relevant legislation, practice and theory, we found that it is differently understood, interpreted and practiced in legal systems, which seem to have started from an identical conceptual position in the implementation of this model of control. It seems to us that it can be a generator for various problems in practice. Hence, we set the main goal of this work, to define the concept of "ex-ante" control, distinguishing it in theoretical terms with other types of control, and most importantly, pointing out the advantages and disadvantages of mismanagement and practicing the same. Although several legal systems will be analyzed, the focus will be on the situation in the Republic of Northern Macedonia.